The impact of asymmetric regulation on product bundling: The case of fixed broadband and mobile communications in Japan - Toshifumi Kuroda; Takanori Ida; Teppei Koguchi (International Telecommunications Society (ITS), 2015)
Product bundling may benefit or harm consumers dependingon the correlation betweenconsumer willingness to pay for the bundledgoods and the levels of market dominance of firms. We develop astructural demand model that allows for correlatedconsumer's willingness to pay and flexible complementarities/substitutabilities. We estimate thismodel using data fromthree surveys conducted bythe JapanMinistry of Internal Affairs and Communications. The estimation results show that fixed broadband and mobile communications are complements for theJapanese telecommunication incumbentbut ambiguousfor competitors. To assess the effect of asymmetric regulation on product bundling by the incumbent, we conduct a counterfactual analysis of a two-stage game where firms choose whether to set bundle discount or not to set for fixed-broadband and mobile communications at stage one and set prices at stage two. The subgame perfect Nash equilibrium ofthetwo-stage game with/without asymmetric regulation shows that mixed-bundling is the dominant strategy for the incumbent. To avoid cannibalization, the incumbent set large discounts for bundle and set high prices for separate goods. Along with high market dominance of the incumbent, this strategy decreases the consumer surplus by 18.8%. Under subgame perfect Nash equilibrium, thediffusion ratesof fixed broadband decreases from 88.9% to 88.0% andthe diffusion rates of mobile communications increases from 95.25 to 95.71%.We also find that pure bundling,asa toolfor leverage,is not a subgame perfect Nash equilibrium.
Keywords: L4; L96; D43; 330; Fixed-to-mobile substitution; Bundles; Leverage; Discrete-Choice Model